KINERJA BAGIAN KEPEGAWAIAN RUMAH SAKIT UMUM DAERAH UNDATA PROVINSI SULAWESI TENGAH - Sjamsudin, Sjamsudin (Katalogis, 2016)
The purpose of this study was to determine the performance of Section Officer Undata Regional General Hospital of Central Sulawesi Province. This study uses the theory of performance by Dwiyanto include Productivity, Quality of Service, Resposivitas, Reponsibilitas, and Accountability. This research is qualitative descriptive. The informants amounted to 7 (seven) determined using purposive technique. Based on the results of research and discussion, it was concluded that the Performance Section Officer Regional General Hospital Undata Central Sulawesi Province as a whole it can be said walking is not optimal, because of the five aspects of bureaucracy performance in rigorous and find facts on the ground, explaining that: productivity performance indicator is not optimal, this is due to the implementation of programs and activities have not been supported by sufficient technical human resources, discipline and participation of personnel in carrying out tasks in Section Officer. Quality of service is not running optimally, it can be seen through complaints from employees against supporting facilities are very inadequate in the sense of an impact on the quality of service, so that despite the continued efforts undertaken by the apparatus of Section Officer remains on implementation is not optimal While performance indicators Responsiveness, Responsibility and Accountability already well underway.